Peningkatan Hasil Belajar Peserta Didik pada Materi Cerita Fiksi menggunakan Model Problem Based Learning berbantuan Wayang Kertas di Kelas IV SDN Sendangmulyo 03 Kota Semarang - Rahmawati, Indah; Purwati, Panca Dewi; Sarini, Kuntarti Endah (Faculty of Teacher Training and Education of Undaris, 2023)
This research aims to describe improving the learning process and outcomes of students in class IV of SD Negeri Sendangmulyo 03, Semarang City on fictional story material through the application of the Problem Based Learning learning model assisted by paper puppets. The data collected in this study were 29 students. This study used a Classroom Action Research (PTK) design. This research was carried out in two cycles through four stages, namely, planning, acting, observing and reflecting. Data collection techniques used in this study include observation, testing, and documentation. Observation sheets are used to determine the improvement of the learning process, namely the ability to reason critically and independently in learning. The test is used to determine the increase in student learning outcomes regarding fictional story material. The data analysis techniques used are descriptive qualitative and quantitative. The results of research in cycle I showed that the number of students who achieved completeness was 17 with a percentage of 59% and 12 students who had not yet completed it with a percentage of 41%. In cycle II there was an increase with 27 students achieving completeness with a percentage of 93% and 2 incomplete students with a percentage of 7%. The average score in cycle I was 72 and cycle II 87.93. The average increase in learning outcomes in pre-cycle and cycle II through the N-gain test was 0.69 in the medium category. Based on these results, it can be concluded that the use of the problem based learning model assisted by paper puppet media can improve students' learning outcomes in class IV fiction story material at SDN Sendangmulyo 03, Semarang City.Keywords: Critical reasoning, independence, problem based learning, paper puppets